Prevalence of four putative periodontopathic bacteria in saliva of a group of Brazilian children with mixed dentition: 1-year longitudinal study - VIVIEN T. SAKAI, MARINELE R. CAMPOS, MARIA APARECIDA A. M. MACHADO, JOSÉ ROBERTO P. LAURIS (IAPD and Blackwell, 2007)
This study aimed at evaluating the prevalence of putative periodontal pathogens ( Actinobacillus actinomycetemcomitans ,Porphyromonas gingivalis,Prevotella nigrescens, Treponema denticola ) in saliva of children with mixed dentition at two different time points, correlating these findings with a clinical parameter of gingival health.